Invasion front-specific expression and prognostic significance of microRNA in colorectal liver metastases - Kahlert, Christoph; Klupp, Fee; Brand, Karsten; Lasitschka, Felix; Diederichs, Sven; Kirchberg, Johanna; Rahbari, Nuh Nabi; Dutta, Shamik; Bork, Ulrich; Fritzmann, Johannes; Reißfelder, Christoph; Koch, Moritz; et al. (Cancer science, 2011)
The tumor edge of colorectal cancer and its adjacent peritumoral tissue is characterized by an invasion front-specific expression of genes that contribute to angiogenesis or epithelial-to-mesenchymal transition. Dysregulation of these genes has a strong impact on the invasion behavior of tumor cells. However, the invasion front-specific expression of microRNA (miRNA) still remains unclear. Therefore, the aim of the present study was to investigate miRNA expression patterns at the invasion front of colorectal liver metastases. Laser microdissection of colorectal liver metastases was performed to obtain separate tissue compartments from the tumor center, tumor invasion front, liver invasion front and pure liver parenchyma. Microarray expression analysis revealed 23 miRNA downregulated in samples from the tumor invasion front with respect to the same miRNA in the liver, the liver invasion front or the tumor center. By comparing samples from the liver invasion front with samples from pure liver parenchyma, the tumor invasion front and the tumor center, 13 miRNA were downregulated. By quantitative RT-PCR, we validated the liver invasion front-specific downregulation of miR-19b, miR-194, let-7b and miR-1275 and the tumor invasion front-specific downregulation of miR-143, miR-145, let-7b and miR-638. Univariate analysis demonstrated that enhanced expression of miR-19b and miR-194 at the liver invasion front, and decreased expression of let-7 at the tumor invasion front, is an adverse prognostic marker of tumor recurrence and overall survival. In conclusion, the present study suggests that invasion front-specific downregulation of miRNA in colorectal liver metastases plays a pivotal role in tumor progression. (Cancer Sci 2011; 102: 1799-1807)
Gesehen am 04.07.2022